IIN strategy : a telecommunications service bureau. (Architecture Technology Corporation, 1991)
Please note this is a Short Discount publication. This report covers the concept, status, and implementation of the IBM Information Network, IIN, IBM appears to be developing a service bureau for telecommunication systems. This service bureau will provide multinational EDI services, as well as other specialized telecommunication services.